Design and performance evaluation of orbital angular momentum metasurface for THz vortex waves generation based on fourier transform - Nasimov, Rashid; Prauzek, Michal; Konecny, Jaromir; Abdelhaq, Maha; Soto-Diaz, Roosvel; Escorcia-Gutierrez, José; Andriukaitis, Darius (Frontiers in Physics, 2025)
IntroductionBecause it is anticipated to be a new physical quantity for communication multiplexing and has significant potential for increasing channel capacity and enhancing spectrum resource utilization, researchers have been looking more closely at orbital angular momentum (OAM). Because of its potential to increase transmission capacity, vortex beams carrying orbital angular momentum (OAM) have recently become a focus of much investigation. One of the main challenges now is how to effectively manufacture OAM in the terahertz (THz) spectrum because existing THz vortex wave generation devices are constrained by only functioning at one frequency, having a small bandwidth, and having low conversion efficiency.MethodsTherefore, this paper proposes a novel OAM metasurface design for generating vortex electromagnetic waves in the THz spectrum. The Pancharatnam-Berry phase idea and the phase superposition principle were used to create a single-layer reflective metasurface and a projected ultra-wideband reflective meta-atom.Results and discussionEach OAM mode in the reflected field was broken down using the Fourier transform, and the purity of the OAM modes was quantitatively examined. The dominant OAM mode had the highest energy weight share (l = −2) in all vortex waves at various frequencies, and the designed metasurface was further optimized to enhance the energy share corresponding to the dominant mode. With its high main mode energy, wide operating bandwidth, and excellent conversion efficiency, the proposed metasurface provides a benchmark for the effective production of wideband THz vortex waves.